East Azarbaijan’s eco-environmental potential for industrialization: functional systems analysis models - Naghdi, F.; Nikkhah, A. (My University, 2014)
The objective was to model and establish East Azarbayjan’s potential for industrial development based on regional eco-environment conditions. A variety of sites in the province were visited, and digital maps of ecological parameters with valuation weight for each layer were generated. The Analytic Hierarchy Process (AHP) was used to weight the influence of several ecological parameters. Results revealed relative restrictions for industrial development in East Azarbayjan, which should be taken into account in planning prospectus industrial expansions. Based on the System Analysis Models, no provincial area was found highly suitable for industrial development, while 21% of the province was suitable, and 79% lacked any suitable potential for industrial development. The data provide novel information and insights into prospective management of industrial investments in light of East Azarbayjan’s eco-environmental unique properties
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Ecological capacity; Industrial development; Systems analysis; East Azarbayjan